SEJARAH KEAGAMAAN DAN SOSIAL MESJID TUA DI MARBAU (LABUHANBATU UTARA) - Muktarruddin Dalimunthe (Center for Research and Development of Religious Literature and Heritage, Agency for Research and Development and Training, Ministry of Religious Affairs of the Republic of Indonesia, 2021)
This study examines how the history of the Kingdom and the old mosque in Marbau District is related to the development of da'wah in Labuhanbatu Utara regency, North Sumatra. The Socio-Historical Approach is used to see the important role of the Kingdom and the Marbau Mosque in the development of da'wah in the community. The establishment of Marbau Mosque in 1850 indicates several important things such as 1) The King of the Marbau Kingdom was a Muslim and became an important identity that the majority of Marbau people are Muslim, 2) the pattern of community religious understanding is also influenced by the Naqsabandiyah Tariqa that was developed in the past. Following the development of Islamic organizations, educational and religious institutions were also developed for the advancement of da'wah within the community. Keyword: Marbau, Old Mosque, Social. Penelitian ini mengkaji tentang bagaimana sejarah kerajaan dan Mesjid tua di Kecamatan Marbau berkaitan dengan perkembangan dakwah di Kabupaten Labuhanbatu Utara Provinsi Sumatera Utara. Pendekatan Sosio Historis digunakan dalam penelitian ini untuk melihat bagaimana peran penting kerajaan dan Mesjid Marbau terhadap perkembangan dakwah di masyarakat. Berdirinya Mesjid raya Marbauahun 1850 menandakan beberapa hal penting di antaranya bahwa raja kerajaan Marbau merupakan orang Islam dan menjadi sebuah identitas penting bahwa masyarakat Marbau mayoritas beragama Islam, corak pemahaman keagaaman masyarakat juga diwarnai dengan tarekat Naqsabandiyah yang sudah berkembang pada masa dahulu. Seiring berkembangnya zaman organisasi keislaman juga ikut mewarnai Marbau, lembaga pendidikan serta keagamaan dikembangkan demi kemajuan dakwah ditengah masyarakat. Kata kunci: Marbau, Mesjid Tua, Sosial.